Dependency profile of the older adult population of a family health unit in northern Portugal - Barbosa, Mónica; Almeida, Luciana; Colaço, Tânia; Santo, Maria Espírito; Santos, Rosa; Martins, Poliana; Sawada, Namie Okino; Martins, Teresa (Frontiers in Public Health, 2025)
BackgroundPopulation ageing is a global phenomenon, associated with declining birth rates and increased life expectancy, with particularly pronounced effects in European countries such as Portugal. In Portugal, the older population increased significantly, reaching 2.48 million in 2020 and the ageing index is estimated to double by 2080. This study aimed to assess the levels of dependency in basic and instrumental activities of daily living among the older population in a Family Health Unit in northern Portugal to plan effective health interventions.MethodA cross-sectional study was conducted with a stratified random sampling by age and gender, encompassing 5.7% of a Family Health Unit users aged 65 years or older. The sample included 212 participants, who were assessed using the Barthel Index for Basic Activities of Daily Living (BADL) and the Lawton-Brody Scale for Instrumental Activities of Daily Living (IADL). Data were analysed using descriptive statistics and inferential methods, including t-tests, ANOVA, and logistic regression, to examine associations between functional dependency and sociodemographic variables.ResultsMost participants were independent in BADL (76.89%) and IADL (75.00%), with dependency increasing significantly with age. Women exhibited higher dependency rates than men in BADL (OR = 2.85; p = 0.012) and IADL (OR = 2.41; p = 0.046). Widowhood was associated with greater dependency in IADL (OR = 2.67; p = 0.032). For each additional year of age, the probability of dependency increased by 10% for BADL and 14.8% for IADL.ConclusionFunctional dependence among older adult individuals in primary healthcare settings highlights the need for targeted interventions to promote autonomy. Gender and age emerged as key predictors of dependency, with women and older adults being particularly vulnerable. These findings underscore the importance of tailored strategies, including physical activity programmes, psychosocial support, and health literacy initiatives, to enhance functional independence and quality of life among older adults.